EFFECT OF SOME RADIO CLIMATIC FACTORS ON DIGITAL TERRESTRIAL TELEVISION SIGNAL IN A SAHEL SAVANNAH CITY OF NIGERIA - Akinbolati, Akinsanmi; Ajewole, Moses Oludare (FUDMA Journal of Sciences, 2020)
This study investigates the effect of some radio climatic factors on the Received Signal Strength (RSS) of a Digital Terrestrial Television Broadcast Station (DTTBS) in Katsina City, Nigeria. The RSS was measured at intervals along selected routes around the station using a digital signal strength meter.  GPS receiver was used to log the line of sight, geographic coordinates and heights of data points from the station. The atmospheric pressure, temperature and humidity corresponding to data points were concurrently measured using a compact weather station whereas the corresponding surface radio refractivity (Ns) values were computed. Data were collected during dry and wet season monthsâ€™ in the year 2017. Results shown that, Ns is inversely proportional to RSS irrespective of routes and seasons with correlation coefficients of -0.51 and -0.57 during dry and wet season months respectively. Higher mean value of, 358.50 (N-units) was deduced during wet compared to the dry season months of 301.20 (N-units). Average atmospheric pressure of 951.92 and 949.61 (hPa) and as well as humidity values of 32.25 and 77.93 %RH were deduced during dry and wet season monthsâ€™ respectively. Findings also show that pressure is inversely proportional to RSS. The overall effects of pressure, temperature and humidity on RSS is better understood using the effect of Ns since the latter is derived from those parameters. This study concludes that the specified radio climatic factors have attenuation effect on UHF signal and should be put into consideration when planning linkâ€™s design and power budgets on the UHF band.
Keywords: Radio Climatic Factors, Surface Radio Refractivity, Digital Terrestrial Television, UHF and Katsina